Optimization problems for construction foundations - Belevičius, Rimantas; Valentinavičius, Saulius (Lietuvos matematikos rinkinys, 2000)
The mathematical models for optimization of grillage-type foundations are presented. Minimising of maximum in absolute value vertical reactive force, bending moment, and reaction-bending moment together is sought. Solutions of a number of problems demonstrate the validity of proposed algorithms.